The Development of Gender Affiliation of Deverbatives Ending on -ež - Vajdlová, Miloslava (Bohemica Olomucensia, 2016)
Action nouns derived from verbs with the suffix -ež (krádež, loupež, etc.) used to be originally masculine in Czech (similarly as in other Slavonic languages). The derivatives have changed their declension affiliation and have merged into feminines in the course of centuries (similarly also in Slovak and Polish).
Keywords: language development; diachrony; Old Czech; Middle Czech; gender affiliation; word-formation; suffix; deverbatives